RNA aptamers specifically interact with the prion protein PrP. - Weiss, S (1997)
We have isolated RNA aptamers which are directed against the recombinant Syrian golden hamster prion protein rPrP23-231 (rPrPc) fused to glutathione S-transferase (GST). The aptamers did not recognize the fusion partner GST or the fusion protein GST::rPrP90-231 (rPrP27-30), which lacks 67 amino acids from the PrP N terminus. The aptamer-interacting region of PrPc was mapped to the N-terminal amino acids 23 to 52. Sequence analyses suggest that the RNA aptamers may fold into G-quartet-containing structural elements. Replacement of the G residues in the G quartet scaffold with uridine residues destroyed binding to PrP completely, strongly suggesting that the G quartet motif is essential for PrP recognition. Individual RNA aptamers interact specifically with prion protein in brain homogenates from wild-type mice (C57BL/6), hamsters (Syrian golden), and cattle as shown by supershifts obtained in the presence of anti-PrP antibodies. No interaction was observed with brain homogenates from PrP knockout mice (prn-p(0/0)). Specificity of the aptamer-PrP interaction was further confirmed by binding assays with antisense aptamer RNA or a mutant aptamer in which the guanosine residues in the G tetrad scaffold were replaced by uridine residues. The aptamers did not recognize PrP27-30 in brain homogenates from scrapie-infected mice. RNA aptamers may provide a first milestone in the development of a diagnostic assay for the detection of transmissible spongiform encephalopathies.